Met opdracht op achterzijde: 'den Heer J v Zutphen, ter herinnering aan 11 mei 1949, ...' Links zittend Jan van Zutphen en Rika Hopper
Met opdracht op achterzijde: 'den Heer J v Zutphen, ter herinnering aan 11 mei 1949, ...' Links zittend Jan van Zutphen en Rika Hopper.